The Impact of the Blended Learning Model on Student Learning Independence during the Learning Process - Syarifudin, Achmad; Sanulita, Henny; Hajati, Erna Noer; Lumbantoruan, Jitu Halomoan (Journal of Education Technology, 2024)
The low level of direct interaction between teachers and students due to the restrictions and distance that must be observed forces students to learn independently. However, not all students have online skills. Therefore, teachers must develop competence by presenting the right model and by government policy, both online and offline. This learning model is blended learning. Teachers have no other choice but to carry out good blended learning management so that learning activities can continue. This research aims to analyze the effectiveness of blended learning management and online skills on students' learning independence. The method in this research is quantitative with an export facto type of research, namely comparative causal research. The data collection technique is by distributing instruments in the form of questionnaires to each teacher respondent by first creating a Google from link. The population in the study were all teachers in one district with a research sample of 90 people from 4 schools spread across one district. Data analysis techniques are correlation and regression. The research results show that blended learning management and online skills have an impact on student learning independence. The impact of the blended learning model and students' online skills is 52.10%. The conclusion is that to increase student learning independence, teachers must carry out the learning process using the blended learning model optimally. The research implies that teachers have implemented the blended learning model by training students who have difficulty online.